Real-World Outcomes of Brolucizumab Treatment in Japanese Patients with Neovascular Age-Related Macular Degeneration: A 12-Month, Multicenter Study - Masayuki Ohnaka; Yoichi Sakurada; Atsushi Hayashi; Kazuaki Kadonosono; Hitoshi Ohno; Ryusaburo Mori; Hidetaka Matsumoto; Ippei Nagamori; Yuki Murata; Tina Maio-Twofoot; Helene Karcher; Hidenori Takahashi (Ophthalmology and Therapy)
Abstract Introduction The aim of this study was to evaluate the real-world outcomes of brolucizumab use in Japanese patients with neovascular age-related macular degeneration (nAMD). Methods PHEASANT was a retrospective, multicenter, single-arm cohort study. The study included 438 patients, of whom 123 were treatment-naïve and 315 were pre-treated. The primary outcome was retinal fluid (subretinal fluid [SRF] and intraretinal fluid [IRF]) resolution at month 12, with change in visual and retinal anatomy parameters and safety assessed as key secondary outcomes. Results At baseline in the treatment-naïve cohort, 10.1% (n = 7/69) of patients were free of retinal fluid, increasing to 62.3% (n = 43/69) at month 12. In the pre-treated cohort, 14.9% (n = 30/201) of patients were free of retinal fluid at baseline, increasing to 43.8% (n = 88/201) at month 12. The median (interquartile range [IQR]) injection interval for pre-treated patients at month 12 was extended by 21 (7.0–35.0) days. The overall intraocular inflammation rate (including the rate of retinal vasculitis/retinal occlusive vasculitis of 0.46% [2/438]) was 8.4% (n = 37/438). Conclusion In a real-world clinical setting, brolucizumab was effective at drying the retina in treatment-naïve and pre-treated Japanese nAMD patients and therefore has the potential to reduce the treatment burden by prolonging injection intervals. Safety outcomes support the overall favorable benefit/risk profile of brolucizumab. ClinicalTrials.gov Identifier NCT06699914.